Synthetic study toward tridachiapyrone B - Cormier, Morgan; Hernvann, Florian; De Paolis, Michaël (Beilstein Journal of Organic Chemistry, 2022)
A convergent approach to the skeleton of tridachiapyrone B is described taking advantage of the desymmetrization of α,α’-dimethoxy-γ-pyrone leading to α-crotyl-α’-methoxy-γ-pyrone in one step. To construct the quaternary carbon of the 2,5-cyclohexadienone of the target, a strategy based on the Robinson-type annulation of an aldehyde derived from α-crotyl-α’-methoxy-γ-pyrone was applied. The grafting of the simplified target’s side chain was demonstrated through an oxidative anionic oxy-Cope rearrangement of the tertiary alcohol arising from the 1,2-addition of a 1,3-dimethylallyl reagent to 2,5-cyclohexadienone connected to the α’-methoxy-γ-pyrone motif.
Keywords: α’-methoxy-γ-pyrone; 2,5-cyclohexadienone; oxy-Cope; quaternary carbon; Robinson-type annulation